G39 Delivering Optimum Care at Journey's End: A Comparison of Barriers to End of Life Care Plans Between a Paediatric Oncology Specialist Centre in the USA and a District General Hospital in UK. (4th June 2013) - Menzies, L; Leith, W
Abstract : End of life care is a challenging but vital aspect for children with life-threatening conditions, requiring parental discussion to plan appropriately. Parents express a need for open and honest information, delivered in a sensitive and timely manner. In adults, advanced care discussions (ACD) result in end of life care closer to patient preference, aligning care with patients' wishes. However there is often patient dissatisfaction regarding the timing and content of ACD. A recent article in Pediatrics ( Durall et al., 2012), identified barriers to conducting ACD for children in a paediatric oncology specialist centre in the USA. Following two challenging cases in our own unit, we assessed our colleagues' views at a district general hospital (DGH) in the UK, to see if similar barriers were pertinent despite contrasting hospital settings. 27 responses to a 23-item survey, adapted from the above article, were compared with findings from the USA centre. Additionally, we explored differences in perceptions between consultants and junior doctors. Similarities between the two hospitals were striking, with 5 of the 6 top barriers to ACD at the USA paediatric oncology centre being replicated at the DGH. Key issues in both settings included clinicians not knowing the right time to address issues, and clinician concern about removing hope. Of note, across the two centres, nurses identified lack of clinician time and lack of importance to clinician as barriers whereas doctors did not. For consultant paediatricians, specific barriers to ACD were differences between clinician/parent/patient understanding of prognosis and clinician uncertainty about prognosis. For junior doctors, specific concerns were not knowing the right time to address the issues or what to say. This study demonstrates that similar barriers to ACD exist internationally. Junior and senior doctors identified particular concerns which could help enhance and target teaching at specific training levels. Findings from nurses suggest that doctors should reflect upon whether sufficient emphasis is given to ACDs and whether priorities should be revised. Reference: Durall A, Zurakowski D, Wolfe J. Barriers to conducting advanced care discussions for children with life-threatening conditions. Pediatrics, 2012(4)e975